Double Fudge - Blume, Judy (New York : Dutton Children's Books, 2002)
His younger brother's obsession with money and the discovery of long-lost cousins Flora and Fauna provide many embarrassing moments for twelve-year-old Peter.
Keywords: Brothers -- Fiction; Family life -- Fiction; Money -- Fiction; Embarrassment -- Fiction; Humorous Stories